Answers

2014-11-12T08:02:04+08:00
Let's try to solve the equation

2x + 11 = 2 - x

now move 11 to the right and change sign and move -x to the left and change sign

2x +x = 2 - 11

Compute

3x = -9

divide by 3 to remove fraction

3x/3 = -9/3

x = -3

As you can see, none of your listed values satisfy the equation.

Let's check is -3 is x

2(-3) + 11 = 2 - (-3)

Compute

-6 + 11 = 5 (positive times negative will be negative; while if same sign will be positive)

5 = 5 Correct (Subtract unlike sign and take the sign of the highest number)

i hope it helps
0